Language acquisition and bilingualism in the family: A case study - Woodward-Smith, Elizabeth; Lorenzo-Modia, María Jesús (Glottodidactica, 2024)
This article will examine some of the variables involved in simultaneous child bilingualism. Family situations are rarely totally alike, and therefore there are no rules about how to manage the bilingual acquisition process. Some recommendations will be considered, though adaptations to each family context are necessary according to a number of factors. Among variables considered are the native languages spoken by the parents (the same or different languages), the country of residence (and if it corresponds to one of the parents’ languages or neither), the prestige attached to either of the languages, the majority or minority status in context, and attitudes shown by the protagonists of each family story and those surrounding them. More than half the world’s population uses two or more languages in everyday life, which implies that bilingualism is by no means a rare phenomenon (Van Wechem & Halbach: 2014). Yet people surrounding the families of children involved in a bilingual situation often voice concerns over the children’s future linguistic competence, worrying that they will speak neither language adequately. However, studies have shown that they are neither delayed in their linguistic development nor disadvantaged by their bilingualism, and in fact their ability to manage more than one language can become an important asset in life. Data from a case concerning three brothers will be presented, showing that their language acquisition broadly followed the same stages as in monolinguals, and that there was no cause for concern over delayed cognitive skills.